The Relevance between White Collar Crime Detention and Digital Legal Application Systems - Firman Wijaya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Gaining an understanding of the relevance between white-collar crime detention and digital legal application systems is the main objective of this study. For us to understand this goal, we have conducted data searches on research evidence released by several well-known journal publication data sources, including publications from Taylor & Francis, Elsevier, Google Books, Sagepub, and magazines and heads of state laws and regulations released by the Law Department and Human Rights of the Republic of Indonesia. Furthermore, our efforts to seek understanding are carried out with the help of an in-depth evaluation, coding, and interpretation system of data until we understand and draw conclusions if the data has answered the core questions of this study. So based on the data and discussion, we can summarize the relevance between legal digital applications and the reduction in white-collar crime in Indonesia. Thus, the results of this study can be helpful in efforts to develop digital law applications in the future.